Invisibility cloak design with artificial intelligence - Muhammad Haikal Bohran (Nanyang Technological University, 2022)
This final year project aims to make use of artificial intelligence. The solver taken into consideration is ‘fmincon – constrained nonlinear minimization’. Previous invisibility cloak research has only studied the ideal condition with a homogeneous backdrop medium The critical features were extracted from the results collected. This report analyses how different parameters affect the performance of the cloak using MATLAB Modelling Software.